Archaeogeophysics State of the Art and Case Studies - El-Qady, Gad; Metwaly, Mohamed (Natural Science in Archaeology, 2019)
This book describes the application of non-destructive geophysical methods in subsurface archaeological features. Such non-destructive methods are magnetometry, electrical resistance, electromagnetic conductivity, magnetic susceptibility and ground penetrating radar. This book also includes the last improvements in instrumentations, data processing, and interpretations of the collected data sets leading to the rapid progress in geophysical applications in the field of archaeological investigations. The book also provides complete case-studies and archaeological interpretation obtained our results carried out in different localities around the world.